KUALITAS PELAYANAN SURAT IZIN MENDIRIKAN BANGUNAN (IMB) RUMAH TEMPAT TINGGAL - resmala, vilia; Hernawan, Denny; Purnamasari, Irma (Universitas Djuanda, 2019)
Service is one of the government's main tasks, which is to provide services as a manifestation of the general duty of government to realize public welfare. However, in reality, in this service, there are still problems that occur in building permits, such as the industrial land used island that is not suitable for building construction. This study aimed to determine the quality of service for Building Construction Permits (IMB) of residential houses in the One-Stop Service and Integrated Services in Bogor city in West Java. This study uses the theory of service quality from Zeithaml, Parasuraman & Berry, which consists of 5 dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The research method uses descriptive methods using Quantitative. Observation, interviews, and questionnaires do data collection. The sample in this study was 63 respondents consisting of the community and service officers. The results obtained an average number of 4.27 with outstanding ratings. It means that overall service quality has been excellent. However, there are still some indicators and dimensions whose value is still lacking, namely the responsiveness dimension of service speed indicators and indicators of the accuracy of the issuance of both. Finally, the researcher suggested that there should be improvements in the speed of service and the accuracy of the letters.